FRI0307 Tbk1 inhibition downregulates expression of interferon type i and the upregulated expression of rig-like receptors and dna-sensing receptors in interferon positive primary sjÖgren's syndrome patients. (12th June 2018) - Bodewes, I.; Huijser, E.; van Helden-Meeuwsen, C.; Tas, L.; Huizinga, R.; Dalm, V.; van Hagen, M.; Groot, N.; Kamphuis, S.; van Daele, P.; Versnel, M.
Abstract : Background: Type I interferon (IFN-I) upregulation is a hallmark of systemic autoimmune diseases like primary Sjögren's syndrome (pSS). Expression of IFN-I is induced by three different receptor families: Toll-like receptors (TLRs), RIG-like receptors (RLRs) and DNA-sensing receptors (DSRs). Previously we have shown increased mRNA levels of TLRs and RLRs in plasmacytoid dendritic cells (pDC) and CD14 +monocytes of IFN-I positive (IFNpos) pSS patients. 1 TANK-binding kinase (TBK1), is an important signalling hub downstream of RLRs and DSRs and leads to production of IFN-I and subsequent induction of interferon-stimulated genes (ISGs). Objectives: Study RLRs and DSRs in pSS and explore the potential of a TBK1 inhibitor to downregulate IFN-I activation. Methods: Expression of RLRs and DSRs was assessed by RQ-PCR and flowcytometry in CD14 +monocytes, BDCA4 +CD123+pDC and CD19 +B cells from IFNpos pSS patients. pDCs from IFNpos pSS patients were analysed by flowcytometry for phosphorylated-TBK1 (pTBK1). PBMCs of pSS patients were cultured with a TBK1 inhibitor, BX795, followed by analysis of IFN-I production and expression of ISGs. Results: In addition to upregulated mRNA levels of RLRs IFIH1 (encoding for MDA5) and DDX58 (encoding for RIG-I), which we previously observed in pDC and monocytes of IFNpos pSS patients, gene expression of IFIH1 and DDX58 was also upregulated in B cells. Upregulation of mRNA levels of the DSRs IFI16 and ZBP1 was observed in monocytes and B cells from IFNpos patients. In pDC protein expression of MDA5, ZBP-1, IFI16 was increased in IFNpos pSS, while there were no differences in RIG-I. In monocytes protein expression of MDA5 was increased and a trend was visible for RIG-I and IFI16. B cells showed increased protein expression of MDA5 and a trend was observed for RIG-I, ZBP-1 and IFI16. These data indicate upregulation of RLRs and DSRs particularly in pDC of IFNpos pSS patients. To further look into the signalling of RLRs and DSRs, phosphorylation of TBK was studied in pDC, the main IFN-I producers, of pSS patients. Increased expression of pTBK1 was observed in pDCs from IFNpos pSS. Upon treatment with BX795, PBMCs from IFNpos pSS downregulated the production of IFN-I and mRNA expression of the ISGs MxA, IFI44, IFI44L, IFIT1 and IFIT3. Conclusions: RLRs and DSRs are upregulated in IFNpos pSS. Signalling of these receptors could be blocked using a TBK1 inhibitor, which reduced IFN-I protein production and expression of ISGs in PBMCs of IFNpos pSS patients. As patented pharmacological inhibitors, amongst others a small molecule inhibitor, are available TBK1 inhibition is indicated as a potential future treatment target for IFNpos pSS. Reference: [1] Maria, et al. ARD2016. Acknowledgements: The research for this manuscript was (partly) performed within the framework of the Erasmus Postgraduate School Molecular Medicine. The authors thank patients and healthy volunteers for taking part in this study. Disclosure of Interest: I. Bodewes: None declared, E. Huijser: None declared, C. van Helden-Meeuwsen: None declared, L. Tas: None declared, R. Huizinga: None declared, V. Dalm: None declared, M. van Hagen: None declared, N. Groot: None declared, S. Kamphuis: None declared, P. van Daele: None declared, M. Versnel Grant/research support from: Research funding Domainex